Pegylated interferon-α2b and ribavirin decrease claudin-1 and E-cadherin expression in HepG2 and Huh-7.5 cells - Rendón Huerta, Erika P.; Torres Martínez, Ana; Charles Niño, Claudia; Rivas Estilla, Ana María; Páez, A.; Fortoul, Teresa I.; Montaño, Luis F. (2013)
Background. Hepatitis C virus (HCV) infection usually results in long-term viremia. Entry of HCV into the he-patocyte requires claudin-1, -6, -9 and occludin. The efficacy of Pegylated interferon-α (PEG-IFN) treatment against HCV infection increased when ribavirin (RBV) was added to the therapeutic scheme. Our aim was to investigate if PEG-IFN plus RBV regulate claudin expression.Material and methods. HepG2, Huh-7 and Huh-7.5 cells were treated with PEG-IFN-α2a or α2b and/or RBV at different times before obtaining the cytosolic, membrane and cytoskeletal fractions. Claudin-1, 3, 4, 6, and 9, E-cadherin and occludin expression was evaluated by Western blot analysis. Transepithelial electrical resistance (TER) was also determined.Results. Claudin-1, 3, 4, 6, E-cadherin and occludin are constitutively expressed mainly in HepG2 cell membrane. Claudin-1 and E-cadherin cell membrane expression diminished after exposure to PEGIFNα2b (50 ng) + RBV(50 μg); the maximal decrease was observed with 200 ng of PEG-IFNα2b + 200 μg of RBV. The effect was less intense with PEG-IFNα2a. The inhibition of claudin-1 and E-cadherin expression in Huh-7 and Huh-7.5 cells was only observed with 200 ng of PEG-IFNα2b + 200 μg of RBV. TER diminished marginally in the HCV containing hepatoma cells with 200 ng of PEG-IFNα2b + 200 ug of RBV. Claudin-1 mRNA expression level was not affected by the combined treatment.Conclusion. The increased therapeutic efficacy of the PEG-IFNα2b plus RBV treatment could be secondary to the inhibition of claudin-1 and E-cadherin cell membrane expression.